STRATEGIC FOOD PRICE DYNAMICS AND THEIR IMPACT ON CONSUMER INFLATION IN WEST NUSA TENGGARA PROVINCE IN 2024 - MUHAMMAD AZIM (Research and Community Service Center of Akademi Bisnis Lombok, 2025)
Food price stability is a crucial indicator for maintaining household economic balance and controlling regional inflation. This study analyzes the relationship between strategic food price fluctuations and consumer inflation levels in West Nusa Tenggara (NTB) Province throughout 2024. Using quantitative descriptive methods with secondary data from the Central Bureau of Statistics (BPS) NTB, this research examines three strategic food commodities: grade I C4 rice, shallots, and beef in three Consumer Price Index (CPI) regions: Mataram City, Bima City, and Sumbawa Regency. The analysis reveals that shallots exhibit the highest volatility with a coefficient of variation of 25.4%, while beef shows the most stability at 1.8%. Rice maintains moderate stability with a CV of 4.3%. Simple correlation analysis demonstrates a positive relationship between average food prices and monthly inflation rates (r = 0.71). Shallots function as a trigger commodity for food inflation, while rice and beef serve as stabilizing commodities. Rising food prices directly impact purchasing power, particularly for lower-middle income groups, where food expenditure exceeds 45% of total consumption. The findings underscore the urgent need for price stabilization policies, improved inter-regional distribution systems, and real-time price monitoring to prevent seasonal food inflation spikes.